Kesesuaian Komponen Pendidikan Karakter dan Jenis Instrumen Evaluasi Pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) Sekolah Menengah Atas di Kota Batam - Said Maskur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
This study aims to determine the suitability of the component of character education and the type of evaluation instruments in natural science (IPA) high school subjects in Batam City. This study involves four phases carried out for the development process, the first phase is carried out using a qualitative method with the Delphi technique with two rounds involving 7 experts in character education each round. This phase aims to identify components and instruments for character education assessment. The second phase is carried out with a quantitative method in which a questionnaire is given to 146 science teachers, to know the components and instruments of character education evaluation in science subjects in the Mengah Atas School. The third phase involves the analysis and presentation of data carried out in two stages, namely qualitative and quantitative analysis using SPSS V. 22.0 and Microsoft Excel The fourth phase has discussed, conclusions and reserves of the study. So the final result of this study is the suitability of the character education component and the type of evaluation instruments in natural science (IPA) high schools in Batam for natural science subjects that the character components are love and responsibility, assessment instruments including attitude scales and document.